Taking care of the body to cure the mind: family-based therapies as attachment-based programs for adolescents with Anorexia Nervosa - Cotugno, Armando; Manaresi, Francesca; Cardi, Valentina (Frontiers in Psychology, 2026)
Anorexia Nervosa (AN) is a severe psychiatric disorder that typically emerges in adolescence and presents a high risk of medical complications and mortality. Early, family-centered interventions are critical in reducing both physical and psychological impairments associated with the illness. This article explores the clinical integration of Family-Based Treatment (FBT) with attachment-informed parenting interventions, particularly Circle of Security—Parenting (CoS-P). We argue that FBT can be conceptualized not only as a behavioral protocol for weight restoration but also as a structured framework for enhancing parental caregiving functions and emotional attunement. Drawing on developmental psychopathology and interpersonal motivational systems theory, we examine how FBT’s emphasis on externalization, parental empowerment, and family meals can be enriched through attachment-based strategies such as video feedback, emotional regulation, and reflective parenting. This integration offers a comprehensive treatment model aimed at restoring the adolescent’s developmental trajectory by supporting both embodied recovery and psychological growth within the family system.